HR Audit Practices in Organizational Governance: A Comparative Perspective from the CIS Region - Liu Yong; Raigul Doszhan (Foundations and Trends in Modern Learning, 2025)
The first level focuses on compliance with regulations and procedures, the second level assesses the performance of personnel functions, and the third level evaluates the alignment of personnel policies with organizational objectives. The proposed methodology is based on a comprehensive analysis of personnel management processes, including recruitment, training, performance evaluation, and career development. The paper also highlights the importance of integrating personnel audit into the overall management system, emphasizing its role in enhancing organizational performance and competitiveness. Based on a thorough examination of theoretical frameworks and the practical context of the Commonwealth of Independent States (CIS), we have identified key objects, methods, and indicators (KPIs) for each level. This article demonstrates that such a comprehensive audit not only helps to identify potential risks and inconsistencies but also enables the evaluation of the effectiveness of HR processes and the alignment of HR strategy with the broader business objectives. The findings of this study can be utilized by managers and HR professionals to implement a systematic approach to assessment and enhance the contribution of the HR function to the creation of company value